Perthes' disease and multiple epiphyseal dysplasia. Issue 622 (August 1977) - Griffiths, H. E.; Witherow, P. J.
Abstract : Five atypical cases were observed amongst ninety children with Perthes' disease, ten of whom had bilateral hip joint involvement. All five were boys, four being under 4 years of age. Four had bilateral hip joint disease, four presented with hip pain, three showing some degree of retardation of bone growth. In one case the hip disorder was familial, and in four there were bony abnormalities elsewhere. Despite the absence of the classic signs of multiple epiphyseal dysplasia, a mild form of this condition is a possible alternative diagnosis for these children. Racial and familial differences are known in the prevalence of Perthes' disease which itself may represent a dysplasia. The pathogenesis of Perthes' disease is still uncertain, although some abnormality of the blood supply to the proximal femoral epiphysis is postulated. That such a vascular defect may be engrafted on to multiple epiphyseal dysplasia is possible, with subsequent joint degeneration which may come to resemble Perthes' disease either clinically or radiologically. A plea is made for the closer study of young children presenting with what may seem to be atypical Perthes' disease.